The Adverse Impact of Tumor Microenvironment on NK-Cell - Hu, Ziming; Xu, Xiuxiu; Wei, Haiming (Frontiers in Immunology, 2021)
NK cells are considered an important component of innate immunity, which is the first line of defensing against tumors and viral infections in the absence of prior sensitization. NK cells express an array of germline-encoded receptors, which allow them to eliminate abnormal cells and were previously considered a homogenous population of innate lymphocytes, with limited phenotypic and functional diversity. Although their characteristics are related to their developmental origins, other factors, such as tumors and viral infections, can influence their phenotype. Here, we provide an overview of NK cells in the context of the tumor microenvironment, with a primary focus on their phenotypes, functions, and roles in tumor micro-environment. A comprehensive understanding of NK cells in the tumor microenvironment will provide a theoretical basis for the development of NK cell immunotherapy.